Compactness in Banach function spaces: Poincaré and Friedrichs inequalities - Bilalov, Bilal; Mamedov, Eminaga; Sezer, Yonca; Nasibova, Natavan (SPRINGER-VERLAG ITALIA SRL, 2025)
In this work, we study the relative compactness of subsets of separable subspaces Xs Omega\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$X_{s} \left( \Omega \right) $$\end{document} of so-called additive Banach function spaces X Omega\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$X \left( \Omega \right) $$\end{document}, which include the rearrangement-invariant spaces defined on the bounded domain Omega subset of Rn\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\Omega \subset R {n}$$\end{document}. We choose Xs Omega\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$X_{s} \left( \Omega \right) $$\end{document} such that the infinitely differentiable functions are dense in it. Moreover, we define the Banach-Sobolev spaces WXsm Omega\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$W_{X_{s} } {m} \left( \Omega \right) $$\end{document} generated by the above subspaces and we study the compactness of embedding between such spaces. The obtained results are used to establish the equivalent norms on these spaces. These results allow us to prove the Poincar & eacute; and Friedrichs-type inequalities for such Sobolev spaces.
Keywords: Additive-invariant; Rearrangement-invariant; Banach-Sobolev spaces; Compactness; Poincar & eacute; inequality; Friedrichs inequality; ORDER ELLIPTIC-EQUATIONS; SOLVABILITY; LEBESGUE; Mathematics